A New Approach to Estimate the Fatigue Limit of Steels Based on Conventional and Cyclic Indentation Testing - David Görzen; Pascal Ostermayer; Patrick Lehner; Bastian Blinn; Dietmar Eifler; Tilmann Beck (Metals, 2022)
For a reliable design of structural components, valid information about the fatigue strength of the material used is a prerequisite. As the determination of the fatigue properties, and especially the fatigue limit σw, requires a high experimental effort, efficient approaches to estimate the fatigue strength are of great interest. Available estimation approaches using monotonic properties, e.g., Vickers hardness (HV), and in some cases the cyclic yield strength, only allow a rough estimation of σw. The approaches solely based on monotonic properties lead to substantial deviations of the estimated σw in relation to the experimentally determined fatigue limit as they do not consider the cyclic deformation behavior. In this work, an estimation approach was developed, which is based on a correlation analysis of the fatigue limit σw, HV, and the cyclic hardening potential obtained in instrumented cyclic indentation tests (CIT). For this, eleven conditions from five different low-alloy steels were investigated. The CIT enable an efficient and quantitative determination of the cyclic hardening potential, i.e., the cyclic hardening exponentCHT eII, and thus, the consideration of the cyclic deformation behavior in an estimation approach. In this work, a strong correlation of σw with the product of HV and |eII| was observed. In relation to an existing estimation approach based solely on HV, considering the combination of HV and |eII| enables the estimation of σw with an enormously increased precision.